Cyber security awareness on social media: knowledge sharing among Orang Asli students / Palaniappan Shamala ... [et. al] - Shamala, Palaniappan; Chinniah, Chinniah; Ahmad, Shamsatun Nahar; Lee, Chang Kerk; Mohd Rick, Abd Malik (UiTM Cawangan Perlis, 2025)
Cybersecurity is becoming more vital as we rely on digital devices and technology to navigate our everyday lives. When access to cyberspace is unrestricted to all levels of age, children use the internet daily for purposes like playing online games, using social media, or even doing their schoolwork. These circumstances have created an environment that makes them vulnerable to cybercrime threats. Therefore, the need to create awareness and training on cybersecurity is vital. However, our awareness program on safety protocol, and information privacy settings in WhatsApp, TikTok, and Instagram was aimed at Orang Asli students because they reside in rural regions with increasing access to digital technologies. Thus, targeted cybersecurity education can help them bridge the knowledge gap and protect them from online risks. The methodology consists of four phases: Phase 1: MCMC as the governmental body runs awareness campaigns, Phase 2 & 3: secondary students from SMK Bekok undergo expert-led training and workshops from lecturers, and Phase 4: create a sustainable educational cycle, wherein secondary students transmit their knowledge to primary students. In each phase, sets of questionnaires with pre and post-tests were distributed to assess the program’s impact. The results showed the program has successfully achieved its objectives of enhancing cybersecurity awareness among Orang Asli students. Knowledge transfer by applying a peer-to-peer approach gained better comprehension, higher engagement, and more effective learning outcomes. In addition, cultivates a collaborative learning atmosphere that advantages both students, simultaneously enriching the educational experience and fostering community engagement within the school